Relaciones interpersonales de los colaboradores y clima organizacional en la empresa Marsan & Asociados SAC -Trujillo, 2022 - Gerónimo Reyna, Vanessa Katterine (2023)
The purpose of this research is to analyze how the interpersonal relationships of employees influence the organizational climate in the company Marsan & Asociados SAC., Trujillo, 2022, having as study population 30 employees, made up of commercial advisors, supervisors, platform manager and administrative. The methods that were used Inductive-deductive and statistical, in addition to the techniques of observation, interview and survey, the instruments were observation record sheet, interview record sheet, questionnaire, bibliographic records, observation guide and interview guide, these facilitated the collection of information, description, understanding and analysis of the variables to be investigated. In the results obtained, it can be shown that there is a direct, significant and moderate relationship between the interpersonal relationships of employees and the organizational climate.